Polycyclic aromatic hydrocarbon exposure and wheeze in a cohort of children with asthma in Fresno, CA - Gale, Sara L; Noth, Elizabeth M; Mann, Jennifer; Balmes, John; Hammond, S Katharine; Tager, Ira B (Journal of exposure science & environmental epidemiology, 2012)
Polycyclic aromatic hydrocarbons (PAHs) are found widely in the ambient air and result from combustion of various fuels and industrial processes. PAHs have been associated with adverse human health effects such as cognitive development, childhood IQ, and respiratory health. The Fresno Asthmatic Children's Environment Study enrolled 315 children aged 6–11 years with asthma in Fresno, CA and followed the cohort from 2000 to 2008. Subjects were evaluated for asthma symptoms in up to three 14-day panels per year. Detailed ambient pollutant concentrations were collected from a central site and outdoor pollutants were measured at 83 homes for at least one 5-day period. Measurements of particle-bound PAHs were used with land-use regression models to estimate individual exposures to PAHs with 4-, 5-, or 6-member rings (PAH456) and phenanthrene for the cohort (approximately 22,000 individual daily estimates). We used a cross-validation-based algorithm for model fitting and a generalized estimated equation approach to account for repeated measures. Multiple lags and moving averages of PAH exposure were associated with increased wheeze for each of the three types of PAH exposure estimates. The odds ratios for asthmatics exposed to PAHs (ng/m 3 ) ranged from 1.01 (95% CI, 1.00–1.02) to 1.10 (95% CI, 1.04–1.17). This trend for increased wheeze persisted among all PAHs measured. Phenanthrene was found to have a higher relative impact on wheeze. These data provide further evidence that PAHs contribute to asthma morbidity.